Juvenile Fish Associated With Pondweed and Charophyte Habitat in the Curonian Lagoon - Bučas, Martynas; Lesutienė, Jūratė; Nika, Nerijus; Skersonas, Andrius; Ivanauskas, Edgaras; Srėbalienė, Greta; Tiškus, Edvinas; Gintauskas, Jonas; Šaškov, Aleksej; Martin, Georg (Frontiers in Marine Science, 2022)
Submerged macrophytes are essential elements of sublittoral ecosystems to maintain a diverse fish fauna. The aim of this study was to assess juvenile fish associated with macrophyte habitats in the Curonian Lagoon by means of modified pop net method. We focused on two dominant littoral habitats with different structure (pondweed and charophyte stands). The pop nets sampling was carried out on two study sites located in the freshwater and oligohaline part of the lagoon in July and September 2019-2020. Our upgraded pop nets reduced the risk of under sampling and are recommended for monitoring fishes since this method has relatively low disturbance on fish behavior and on the habitat itself. The most efficient time of sampling with pop nets in shallow macrophyte habitats is at night, where at least 4 samples collected are sufficient to represent the biggest part (> 70%) of the fish assemblage, but the sampling covering different times of day is recommended. In total, 14 juvenile species were recorded, where perch and European roach dominated (respectively 48% and 24%). Half of the species (8) were associated with macrophyte stands, although water salinity and temperature were the most important factors explaining the variance of fish abundance followed by the sampling time and the biomass of macrophytes. Based on the abundance and the duration of species within these habitats, European roach, nine-spined and three-spined stickleback were mainly associated with the pondweed biomass and stands, while spined loach, round goby, perch, ruffe and gudgeon were mainly associated with the charophyte biomass and stands. The increase of charophyte stands since 2005 affected the fish assemblage where it should have enhanced the abundance of perch, ruffe, spined loach and partly round goby.